Current status legal regulation of freedom religion in Ukraine and prospects of its improved - Сопілко, Ірина Миколаївна; Возняк, Ірина Дмитрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article dealing with the questions correlation between the concepts freedom of conscience and religion, religion. The authors analyze the present state of legal regulation mentioned sphere and ways on perfection of legal regulation freedom of conscience in Ukraine